Rule-Making Custom and its Effect in Limiting the will with Emphasizing Family Rights - Hosein Javar; Mohaddeseh Osuli Yamchi; Mohammad Ashaiery Monfared (فقه و حقوق خانواده)
Custom may be the source of obligations and commitment in the field of creating rules, in addition to explaining and removing ambiguity from issues. "Scope of obligations", "degree" and "binding conditions of custom" and its relationship with the common and customary, as well as its conflict with regulations are important questions in the field of rule-making custom (research issue). Despite the wide scope of application of rule-making custom, due to the lack of sufficient study resource, there are many ambiguities in front of it (the necessity of research). In the light of the analysis of the content of the provisions of the custom and determining the demarcation between the types of custom and paying attention to the hierarchy of the rules (processing method) it becomes clear, aside with the criterion of being known (the material element) and its dynamism and flexibility, in the requirements related to behaviors, foundations and common and customary orders, it is necessary to include rationality and the absence of legal and religious prohibitions in it. Therefore, the provisions of the rule-making custom, if it would be optional, take precedence over the supplementary laws, and its rank is after the mandatory rules and contracts. Such a custom is objectionable and an agreement contrary to it is possible, and if the rule-making custom is mandatory, it takes precedence over the contracts and wills of individuals. Such custom is not objectionable and an agreement to the contrary is not possible. Some examples of arbitrary custom are rejected. . In case of a conflict between optional or mandatory custom with mandatory laws and Shari'a rulings, the case is considered as an example of a rejected custom. Of course, if the subject custom is according to the law, its handling will also be within the supervisory jurisdiction of the Supreme Court (research achievements).